Detection of Herpesvirus anguillae (AngHV‐1) in European eel Anguilla anguilla (L.) originating from northern Poland—assessment of suitability of selected diagnostic methods. Issue 11 (24th August 2017) - Nguyen, Tuan Thuc; Jin, Yeonhwa; Kiełpińska, Jolanta; Bergmann, Sven M.; Lenk, Matthias; Panicz, Remigiusz
Abstract: The Community Action Plan requests EU member states to implement measures that ensure the recovery of the severely depleted European eel stocks. One of the main threats is posed by Anguillid herpesvirus 1 (AngHV‐1) leading to increased mortality in both wild and farmed eels. Following recommendations of the OIE to minimize the risk of obtaining false‐negative results, the main aim of the study was to optimize diagnostic methods for AngHV‐1 detection using conventional PCR, nested PCR and in situ hybridization assay. While 53.3% of the individual organ samples were tested positive for AngHV‐1 by PCR, the additional virus analysis via nested PCR revealed that the actual prevalence was 93.3%. In the cell cultivation passages, a cytopathic effect was hardly found in the first two rounds. In the third passage onto cell cultures, a lytic CPE was detected. The identification and confirmation of the viruses obtained from cell cultures as well as directly from the organ tissues were proceeded by PCR, nested PCR and sequencing of the PCR products. While no positive signal was detectable in the first round by PCR using samples from the third cell culture passages, the nested PCR provided weak but visible positive signals.